UJI SIFAT ELEKTRONIK FILM Bax Sr1-xTiO3 DENGAN METODE WERNER - Endang Rancasa (Jurnal Biofisika, 2013)
In this study, BaxSr1-xTiO3(BST) films were grown on p-silicon substrates using chemical solution deposition (CSD) and were annealed at 850oC for 15 hours. Then contact were made on its. Measurement of electrical properties has been observed using sourcemeter and then its were analyzed using werner method to extract seriesresistance and ideality factor. Then value of series resistance w as used to correct voltage data Vd. Then graphs of Vd – Ln I were analyzed to extract saturation current, barrier potential and ideality factor. The increasing of mol fraction of Ba caused increasing in saturation current and reduces value of series resistance, ideality factor and barrier potential.